Association of Cd40 (rs1883832) SNP in some Iraqi patients with Rheumatoid Arthritis and their correlation with disease activity - Sattar Brissm Hassan; Hanaa Naji Abdullah; Khalied Yassen Zakair (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the genotyping of CD40 gene (rs1883832) single nucleotide polymorphism (SNP) among rheumatoid arthritis patients, and to investigate its correlation with disease activity. Method: The case-control study was conducted at Baghdad Teaching Hospitals, its affiliated Rheumatology units and Al-Yarmouk Teaching Hospital, Baghdad, Iraq, from July 2020 to May 2021, and comprised adult females with rheumatoid arthritis in group A and healthy controls in group B. The disease activity in group A was evaluated using the Disease Activity Score in 28 Joints scale. Samples from both groups were genotyped using TaqMan Assay for cluster of differentiation gene rs1883832 single nucleotide polymorphism. Data was analysed using SPSS 28. Results: Of the 118 participants, 76(64.4%) were in group A with mean age 45.38±1.23 years, and 42(35.6%) were in control group B with mean age 46.48±2.02 years. At cluster of differentiation gene rs1883832 single nucleotide polymorphism, there was a non-significant difference in the frequency of T and A alleles as well as in TT, AA and TA in group A patients compared to group B controls (p>0.05). Rheumatoid factor and C-reactive protein concentrations with TT, TA and AA genotypes in group A were significantly higher in group A compared to group B (p<0.05). Within group A, there was a significant increase in the TT genotype and a significant decrease in the TA genotype in severe cases compared to mild cases. (p<0.05). Conclusion: The cluster of differentiation gene rs1883832 single nucleotide polymorphism T allele was found to be a risk factor for rheumatoid arthritis and disease severity. The TT and AA alleles acted as protective factors. Keywords: Polymorphism, Disease activity, Genotype.